Smoking and Returns to Education: Empirical Evidence for Germany - Julia Reilich (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Looking at smoking-behavior it can be shown that there are differences concerning the time-preference-rate. Therefore this has an effect on the optimal schooling decision in the way that we assume a lower average human capital level for smokers. According to a higher time-preference-rate we suppose a higher return to education for smokers who go further on education. With our empirical fondings we can confirm the presumptions. We use interactions-terms to regress the average rate of return with the instrumentvariable approach. Therefore we obtain that smokers have a significantly higher average return to education than non-smokers.
Keywords: J24; J31; I21; 330; Returns to education; Human Capital; Smoking Effects; Rauchen; Bildungsverhalten; Bildungsertrag; Deutschland